2018
DOI: 10.21307/pjm-2018-028
|View full text |Cite
|
Sign up to set email alerts
|

New Gene Responsible for Resistance of Clinical Corynebacteria to Macrolide, Lincosamide and Streptogramin B

Abstract: The subject of the study was phenotypic marking of the antibiotic susceptibility and MLSB resistance mechanism in Corynebacterium spp. isolated from human skin (18 isolates) and from clinical materials (19 isolates). The strains were tested for the presence of the erm(A), erm(B), erm(C), erm(X), lnu(A), msr(A), msr(B) and mph(C) genes. Clinical isolates showed wide resistance to antibiotics. In 89% clinical isolates and 72% skin microbiota a constitutive type of MLSB resistance was found. In 12 clinical isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The MLS phenotype (resistance to Macrolides, Lincosamides, Streptogramin) is a mechanism frequently observed in coagulase-negative staphylococci [ 59 , 60 ]. It is also widely seen in corynebacteria of clinical importance, such as Corynebacterium diphtheriae , Corynebacterium xerosis , C. jeikeium , C. pseudodiphtheriticum , C. amycolatum , C. urealyticum [ 61 , 62 , 63 , 64 , 65 ], and C. striatum .…”
Section: C Striatum Resistomementioning
confidence: 99%
“…The MLS phenotype (resistance to Macrolides, Lincosamides, Streptogramin) is a mechanism frequently observed in coagulase-negative staphylococci [ 59 , 60 ]. It is also widely seen in corynebacteria of clinical importance, such as Corynebacterium diphtheriae , Corynebacterium xerosis , C. jeikeium , C. pseudodiphtheriticum , C. amycolatum , C. urealyticum [ 61 , 62 , 63 , 64 , 65 ], and C. striatum .…”
Section: C Striatum Resistomementioning
confidence: 99%
“…The methylation of rRNA can lead to the change of ribosome con guration, resulting in the decrease in the binding ability of macrolides, glycosamides, and streptogramins B to bacterial ribosome targets [7]. Since these antibiotics have the same or overlapping target sites, bacteria can simultaneously cross-resistant to these three types of antibiotics, known as macrolide-lincosamide-streptogramin B (MLS B ) resistance [8,9]. The common drug-resistance related genes in Streptococcus are ermA, ermB, and ermC [10].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that they may be widespread in other Streptococcus, including Streptococcus agalactiae (Group B Streptococcus, GBS) [17]. In addition, a new e ux system encoded by mreA, unlike the Mef pump [18], has been characterized in a single Streptococcus agalactiae strain resistant to 14, 15 and 16-membered macrolides [9,14,17].…”
Section: Introductionmentioning
confidence: 99%